2002
DOI: 10.1136/thorax.57.7.586
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide in chronic airway inflammation in children: diagnostic use and pathophysiological significance

Abstract: Background: The levels of exhaled and nasal nitric oxide (eNO and nNO) in groups of patients with inflammatory lung diseases are well documented but the diagnostic use of these measurements in an individual is unknown. Methods: The levels of nNO and eNO were compared in 31 children with primary ciliary dyskinesia (PCD), 21 with non-CF bronchiectasis (Bx), 17 with cystic fibrosis (CF), 35 with asthma (A), and 53 healthy controls (C) using a chemiluminescence NO analyser. A diagnostic receiver-operator character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
153
1
5

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(168 citation statements)
references
References 20 publications
9
153
1
5
Order By: Relevance
“…For the confirmed PCD group with defined ultrastructural defects in the ciliary axonemes, the mean nNO level (20.0 nl/ min) is less than 10% of the mean nNO measurement for healthy control subjects (304.6 nl/min) with minimal overlap. Previous reports in smaller subsets show a similar magnitude of difference between PCD and healthy control subjects (7)(8)(9)(10)(11)(12). The cutoff value defined in this study (77 nl/min) is slightly lower than what was identified in our earlier study that examined a smaller patient population (7).…”
Section: Original Researchmentioning
confidence: 57%
See 3 more Smart Citations
“…For the confirmed PCD group with defined ultrastructural defects in the ciliary axonemes, the mean nNO level (20.0 nl/ min) is less than 10% of the mean nNO measurement for healthy control subjects (304.6 nl/min) with minimal overlap. Previous reports in smaller subsets show a similar magnitude of difference between PCD and healthy control subjects (7)(8)(9)(10)(11)(12). The cutoff value defined in this study (77 nl/min) is slightly lower than what was identified in our earlier study that examined a smaller patient population (7).…”
Section: Original Researchmentioning
confidence: 57%
“…The nNO values in some of the patients with CF, however, did overlap with PCD values, which has been described in other studies (7)(8)(9)11). Therefore, CF must be excluded by a quantitative pilocarpine iontophoresis sweat test or CFTR genotype testing in all individuals with nNO measurements below the cutoff values.…”
Section: Original Researchmentioning
confidence: 80%
See 2 more Smart Citations
“…For example, nasal NO is extremely low in primary ciliary dyskinesia (PCD) [4] and in cystic fibrosis [24]. In fact, a nasal NO test is currently part of the clinical routine at the national centre for PCD in the UK [25]. In allergic rhinitis the picture is less clear.…”
Section: Discussionmentioning
confidence: 97%